Revisiting the fate of buds: size and position drive bud mortality and bursting in two coexisting Mediterranean Quercus species with contrasting leaf habit - Alla, Arben Q.; Julio Camarero, J.; Palacio, Sara; Montserrat-Martí, Gabriel (TREES-STRUCTURE AND FUNCTION, 2013)
Understanding the relationships between bud size and position and bud fate through time is crucial for identifying and subsequently modeling the mechanisms underlying tree architecture. However, there is a lack of information on how bud size drives crown architectural patterns in coexisting tree species. We studied bud demography in two coexisting Mediterranean oak species with contrasting leaf habit (Quercus ilex, evergreen; Q. faginea, deciduous). The main objective was to analyse the effect of bud size on the fate of buds with different positions along the shoot (apical, leaf axillary and scale-cataphyll axillary buds). The number, length and position of all buds and stems were recorded in marked branches during 4 years. Study species presented different strategies in bud production and lifespan. The evergreen species showed greater mortality rate than the deciduous one, which produced larger buds. Bud size and position were highly related since apical buds where longer than axillary ones and bud length declined basipetally along the stem. Apical buds had also higher chances of bursting than axillary ones. Within positions, longer buds presented a higher probability of bursting than shorter ones, although no absolute size threshold was found below which bud bursting was impaired. In Q. ilex, four-year-old buds were still viable and able to burst, whereas in Q. faginea practically all buds burst in their first year or died soon after. Such different bud longevities may indicate contrasting strategies in primary growth between both species. Q. ilex is able to accumulate viable buds for several ages, whereas Q. faginea seems to rely on the production of large current-year buds with high bursting probability under favourable environmental conditions.
The following values have no corresponding Zotero field: pub-location: 233 SPRING ST, NEW YORK, NY 10013 USA publisher: SPRINGER
Keywords: Bud demography; Bud position; Bud size; Budburst; Quercus faginea; Quercus ilex subsp ballota